Traits of trees for cooling urban heat islands: A meta-analysis - Rahman, Mohammad A.; Stratopoulos, Laura M.F.; Moser-Reischl, Astrid; Zölch, Teresa; Häberle, Karl-Heinz; Rötzer, Thomas; Pretzsch, Hans; Pauleit, Stephan (Building and environment, 2020)
A more detailed understanding of the micro-climatic thermal benefits of different urban tree species and the retrospective species characteristics is necessary to guide management decisions. In this review, we focused specifically on empirical data collected at ground level for below-canopy surface temperature (ST) and transpiration cooling (AT), using a meta-analysis method. Tree canopy density was clearly identified as the most influential driver of different mechanisms of cooling benefits. Secondly, climate of the cities where the trees were grown showed significant impacts on cooling potentials: trees grown in Oceanic and Continental climates showed a higher cooling potential compared to trees grown in Mediterranean climate for AT and sub-tropical climate for ST. Thirdly, tree growth in size and ground surface cover showed significant impact. ST decreases almost linearly with the increase of canopy density; however, the rate is significantly lower over transpiring grass surfaces. Transpiration of trees planted over grass was ten times higher (4.15 g m−2 min−1) compared to a tree planted in paved cut-out pits (0.44 g m−2 min−1). Moreover, diffuse porous wood anatomy and trees originating from temperate and resource-rich forests showed better cooling potentials. Among the leaf traits, dark green leaves, < 0.15 mm of thickness showed higher AT and ST benefit. The review pointed out the lack of standardized study protocols in determining tree cooling benefits and empirical data, particularly at tropical and sub-tropical climate. Finally, the study suggested some recommendations for plantings that optimize the cooling benefits from urban greenspaces. •Determinant variables about tree species cooling potential have been investigated.•Surface (ST), transpiration air-cooling (AT) and human comfort (TC) was reviewed.•Leaf area index showed a positive correlation with all three mechanisms of cooling.•Surface temperature reduction was more over asphalt than grass or building walls.•Darker, thin leaved species with diffuse porous wood anatomy provided better AT.